Differential quadrature free vibration analysis of sandwich plates with curvilinear fiber variable stiffness composite face sheets - Zhou, Zhenyu (Frontiers in Materials, 2025)
Free vibration calculations of Sandwich plates with curvilinear fiber variable stiffness composite face sheets usually require a significant computing effort to obtain a high computational accuracy. An improved approach integrating the differential quadrature method (DQM) and first-order shear deformation theory (FSDT) is introduced in this work. The skins of sandwich plates are composed of one or several layers of variable stiffness composite laminates (VSCL) with fiber paths assumed to follow a specific linear pattern. The FSDT and von Kármán strain–displacement relationship were used to derive the governing equations of the sandwich plate, and DQM was applied to discretize such governing equations and solve for the fundamental frequency of the sandwich plate. The computational results were verified and compared with other FSDT–based computational results, and there was good agreement with the suggested model. Also, the variation patterns of the natural frequency under different parameters such as fiber orientation angles, boundary conditions, number of layers, and core/skin thickness were investigated. The novelty of this study lies in the first application of an integrated DQM-FSDT approach to the free vibration analysis of sandwich plates with variable-stiffness curvilinear fiber composites. Notably, this method attains accuracy comparable to higher-order models (<5% error) with merely a 19 × 19 mesh. Key results demonstrate that optimizing the fiber path can enhance the fundamental frequency of VSCL sandwich plates by up to 32.7% (CFFF boundary), providing an efficient design tool for vibration control of aerospace lightweight structures.